Word Cloud Visualization of Media Reactions to USAID Shutdown - Rahmadani, Sinta; Yuadi, Imam (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
The closure of USAID prompted various reactions by the media, which in turn affected public opinion and ongoing policies. This research investigates how media narratives cover the shutdown of USAID using word cloud visualization to capture themes and sentiments. The research attempts to find: What are the dominant media narratives regarding the shutdown? Using tokenization, stopword elimination, and frequency analysis before generating a word cloud to illustrate prominent words. The data shows that US media focuses on government spending, foreign aid, employment, and diplomatic activity, which all influence the public perception of the shutdown. The study argues that computational text analysis aids in the understanding of media discourse and sentiments on policies, which help policymakers and scholars concerned with public opinion and policy discourse on international aid and development issues. This study advances the field of media by expanding the scope of the study of visual politics and political communication. The analysis reveals that the conversation revolves around government activities, consequences of foreign aid, workforce considerations, and spatial politics, with “funding,” “security,” and “diplomatic” standing out the most. The analysis of the media coverage shows that the shutdown is framed as a political as well as an economic crisis, constructing a narrative that is later used in public discourse and policy discussions. This project adds to the body of work on media by employing visual analysis in the study of political communication and analyzing media framing from a computational perspective.